HUBUNGAN TINGKAT PENGETAHUAN, SIKAP, TINDAKAN IBU TERHADAP INFEKSI CACING SOIL TRANSMITTED HELMINTH PADA SISWA SD NEGERI 23 PASIR SEBELAH TAHUN 2023 - Rahma Triyana; Utari Felia Anggaraini; Nurwiyeni, Nurwiyeni; Ruhsyahadati, Ruhsyahadati; Nana Liana; Prima Adelin; Melya Susanti; Rifkind Malik; Roland Helmizar; Muhammad Rizki Saputra; Alif Dhuha (Yayasan Nusantara Hasana Berdikari, 2025)
Soil Transmitted Helminth (STH) infections remain a major public health issue in Indonesia, particularly among elementary school children. Behavioral and socioeconomic factors, including mothers' knowledge, attitudes, and practices, are suspected to influence the incidence of these infections. This study aimed to determine the relationship between mothers’ level of knowledge, attitudes, and practices and the incidence of STH infections among students of SD Negeri 23 Pasir Sebelah, Koto Tangah, Padang, in 2023. An analytic observational study with a cross-sectional design was conducted involving 87 first to third-grade students and their mothers, selected through total sampling. Data were analyzed using the Chi-square test. The results showed that 6.9% of the children were infected with STH. Most mothers demonstrated good levels of knowledge, attitudes, and practices. There were significant associations between mothers’ knowledge (p=0.028), attitudes (p=0.000), and practices (p=0.000) and the incidence of STH infections. In conclusion, mothers’ knowledge, attitudes, and practices were significantly associated with STH infections among elementary school children, highlighting the importance of family health education in preventing parasitic infections.